Efektifitas Pelaksanaan Peraturan Mahkamah Agung Nomor 3 Tahun 2017 di Pengadilan Agama Marisa - Lulu Sarini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
This study aims to determine the effectiveness of the implementation of Supreme Court Regulation No. 3 of 2017 Concerning Guidelines for Judging Women Against the Law (PERMA). This research is a field research with data collection methods such as observation, interview and documentation study. The collected data is processed and analyzed with qualitative descriptive. The results of the study showed that the Judges at the Marisa Religious Court in deciding divorce divorce cases before and after the issuance of the regulation had not yet enumerated the request for the Petitioner to pay the burden. However, due to the Circular of the Mahkamah Agung Number 1 of 2017, there is a wife's right to pay. In relation to the effectiveness of the PERMA, it has been effective in enforcing gender justice in the Marisa Religious Court. In certain divorce divorce cases, the wife is present and submits a reconciliation claim regarding livelihood at the hearing, and verstek and case matters where his wife does not submit a liability claim then the PERMA is ineffective or not applied.